Systemic Scleroderma - Advances in Understanding and Management - Abduraxmanova Nargiza Mirza Baxtiyorovna; Botirbekov Abdurashid Nazarkulovich (Genius Journals, 2024)
Systemic scleroderma, also known as systemic sclerosis (SSc), is a rare autoimmune disease characterized by fibrosis of the skin and internal organs, posing significant challenges in diagnosis, treatment, and management. Recent advancements in research have significantly expanded our understanding of the disease pathogenesis, genetic predisposition, environmental triggers, biomarkers, and treatment strategies. The pathogenesis of systemic scleroderma involves complex interactions between dysregulated immune responses, endothelial dysfunction, vascular abnormalities, and aberrant extracellular matrix remodeling pathways. Genetic susceptibility factors, including variants within immune regulatory genes and the human leukocyte antigen (HLA) region, contribute to disease susceptibility and phenotype expression. Environmental triggers, such as viral infections, occupational exposures, medications, and lifestyle factors, may act as catalysts for disease initiation and progression. Identification of reliable biomarkers for disease activity, severity, and progression is essential for optimal disease monitoring and management. Serum biomarkers, including cytokines, chemokines, and autoantibodies, offer promise for predicting disease outcomes, guiding treatment decisions, and monitoring treatment response. Imaging biomarkers, such as high-resolution computed tomography (HRCT) and magnetic resonance imaging (MRI), provide valuable insights into internal organ involvement and disease progression. Systemic scleroderma represents a complex autoimmune disease with significant heterogeneity in clinical presentation and disease course. Advances in our understanding of disease pathogenesis, genetics, biomarkers, and treatment strategies have paved the way for personalized and targeted interventions aimed at improving outcomes and quality of life for individuals living with systemic scleroderma. Further research is needed to elucidate the underlying mechanisms driving disease progression and to develop novel therapeutic approaches to address the unmet needs of patients with systemic scleroderma.
Keywords: systemic scleroderma; autoimmune disease